TANGGUNG JAWAB DEVELOPER DALAM PEMBANGUNAN PERUMAHAN DI DAERAH RAWAN BENCANA IMPLIKASINYA TERHADAP PERLINDUNGAN KONSUMEN - Usman, Muhammad; Chairunnisa, Nakeisha; Azzahra, Devyta; Cynthia, Veronica (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Housing development in disaster-prone areas faces various legal challenges related to developer responsibility and consumer protection. This research aims to analyze the limits of developer responsibility in providing housing that complies with technical standards and the legal implications for the protection of consumers who experience losses. This research uses a normative juridical method with a statutory approach (statue approach) and case (case approach). The research results show that even though there are regulations governing standards for disaster-resistant buildings, such as Law Number 28 of 2002 concerning Buildings and Law Number 1 of 2011 concerning Housing and Settlement Areas, there are still many developers who ignore these standards for the sake of cost efficiency. In some cases, developers can be relieved of responsibility by pretexting force majeure which makes it difficult for consumers to obtain compensation. To protect consumers, strengthening regulations, increasing government supervision, and more effective dispute resolution mechanisms are needed. With clearer legal certainty, it is hoped that a balance between developer interests and consumer rights can be realized.